Writing to Learn Strategies: Improving Students’ Critical Thinking and Science Communication Skills in Wave Concepts - Evelina Astra Patriot; Putri Anggraini (PAEDAGOGIA, 2025)
This research analyses the impact of writing to learn strategies on students' critical thinking and science communication skills, particularly on light and sound waves. The research employed a quasi-experimental approach, utilising a nonequivalent control group design. The study involved students from a high school in Palembang, with 32 participants in the experimental group and 32 in the control group. Before being tested on students, the critical thinking skills test items and science communication item sheets were evaluated by three experts. The research used pretest and posttest scores to assess the enhancement of students' cognitive abilities and critical thinking skills. The results showed that the experimental class showed significantly higher essential thinking abilities than the control class. The calculation of Cohen's d effect size is 1.5, which is included in the large category. The results of the analysis show that the test items can be used to test students. The results showed that students in the experimental class wrote conclusions well, but some wrote them less clearly due to repetition. The study concluded that the writing to learn approach effectively improved students' critical thinking skills, indicating that the writing to learn strategy can be an effective learning method. These findings suggest that integrating writing-based approaches in physics instruction can support the development of 21st-century skills. For future education practice, the test items can be combined with education technology, like flipbooks, to assess the development of students' critical thinking and communication skills